Studies of Bolivian Ptiliidae (Coleoptera) 2: The subfamily Acrotrichinaeincluding two new genera Petrotrichis and Microtrichis, and eight new species of Acrotrichis - Darby, Michael (Zootaxa, 2015)
This is the second report on a collection of Ptiliidae from Bolivian forest leaf litter made by Dr Petr Baňař of the Brno Museum (Czech Republic) in 2013. A small collection of Bolivian Acrotrichis in the Natural Museum, London, made by H. Mendel and M.V.L. Barclay in 2004 is also included. Two new monotypic genera are described Petrotrichis gen. n. (Acrotrichini), type species P. rotundata sp. n., and Microtrichis gen. n. (Nephanini), type species M. pectana sp. n., together with eight new species of Acrotrichis: A. armillata sp. n., A. cincinna sp. n., A. cornuta sp. n., A. corpulenta sp. n., A. inlecebrosa sp. n., A. linea sp. n., A. nashi sp. n. and A. segmenta sp. n..